Development Of Esl Speaking Proficiency Assessment For Undergraduates - Saeed, Karwan Mustafa (2018)
English is regarded as an asset that can result in success in the twenty-first-century job market. Hence, mastering the art of speaking to many language learners is seen as the most important language aspect when learning the English language. Speaking assessment has made significant inroads into the field of language teaching and pedagogy in pursuit of improvement. It is vital that instructors assess their students’ speaking proficiency continuously and therefore, test results must assist instructors to determine students’ speaking proficiency. However, the current assessment based on grades does not provide specific information regarding students’ specific speaking proficiency. The grade provided does not indicate information on how to help students enhance their speaking proficiency.